Challenges in chemotherapy delivery: comparison of standard chemotherapy delivery to locoregional vascular mass fluid transfer. (6th March 2018) - Lane, Rodney J; Khin, Nyan Y; Pavlakis, Nick; Hugh, Thomas J; Clarke, Stephen J; Magnussen, John; Rogan, Chris; Flekser, Roger L
Standard intravenous chemotherapy delivery to neoplasms relies on simple diffusion gradients from the intravascular to the interstitial space. Systemic perfusion creates untoward effects on normal tissue limiting both concentration and exposure times. Regional intra-arterial therapy is limited by drug recirculation and vascular isolation repeatability and does not address the interstitial microenvironment. Barriers to delivery relate to chaotic vascular architecture, heterogeneous fluid flux, increased interstitial and variable solid tumor pressure and ischemia. To address these difficulties, a delivery system was developed allowing mass fluid transfer of chemotherapeutic agents into the interstitium. This implantable, reusable system is comprised of multiple independently steerable balloons and catheters capable of controlling the locoregional hydraulic and oncotic forces across the vascular endothelium.